Evidence of a sudden increase in the nuclear size of proton-rich silver-96 - M. Reponen (Nature Portfolio, 2021)
Laser spectroscopic measurements of isotopes near the doubly-magic 100-Sn are challenging due to difficulties in their production. Here the authors measure the ground state charge radius of the proton-rich 96-Ag isotope and find a discontinuity in the nuclear size when crossing the neutron number N equal to 50.